The temporal relationship between cancer and adult onset anti-transcriptional intermediary factor 1 antibody–positive dermatomyositis. (7th December 2018) - Oldroyd, Alexander; Sergeant, Jamie C; New, Paul; McHugh, Neil J; Betteridge, Zoe; Lamb, Janine A; Ollier, William E; Cooper, Robert G; Chinoy, Hector
Abstract: Objectives: To characterize the 10 year relationship between anti-transcriptional intermediary factor 1 antibody (anti-TIF1-Ab) positivity and cancer onset in a large UK-based adult DM cohort. Methods: Data from anti-TIF1-Ab-positive/-negative adults with verified diagnoses of DM from the UK Myositis Network register were analysed. Each patient was followed up until they developed cancer. Kaplan–Meier methods and Cox proportional hazard modelling were employed to estimate the cumulative cancer incidence. Results: Data from 263 DM cases were analysed, with a total of 3252 person-years and a median 11 years of follow-up; 55 (21%) DM cases were anti-TIF1-Ab positive. After 10 years of follow-up, a higher proportion of anti-TIF1-Ab-positive cases developed cancer compared with anti-TIF1-Ab-negative cases: 38% vs 15% [hazard ratio 3.4 (95% CI 2.2, 5.4)]. All the detected malignancy cases in the anti-TIF1-Ab-positive cohort occurred between 3 years prior to and 2.5 years after DM onset. No cancer cases were detected within the following 7.5 years in this group, whereas cancers were detected during this period in the anti-TIF1-Ab-negative cases. Ovarian cancer was more common in the anti-TIF1-Ab-positive vs -negative cohort: 19% vs 2%, respectively ( P < 0.05). No anti-TIF1-Ab-positive case <39 years of age developed cancer, compared with 21 (53%) of those ≥39 years of age. Conclusion: Anti-TIF1-Ab-positive-associated malignancy occurs exclusively within the 3 year period on either side of DM onset, the risk being highest in those ≥39 years of age. Cancer types differ according to anti-TIF1-Ab status, and this may warrant specific cancer screening approaches.